Fast phase separation induced passive radiative cooling polymer thin films and methods of making the same
Patent Information
- Application Number
- CN202611292318.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-25
- Publication Date
- 2026-10-09
AI Technical Summary
[0005]在辐射制冷材料领域,解决了现有辐射制冷材料制备工艺复杂、不可生物降解或难以回收、光谱性能与可持续性之间存在权衡等问题,提供了一种简便、普适、可循环再生的高性能辐射制冷薄膜及其制备方法
[0020]高太阳光反射性能。本发明制备的纯聚合物多孔薄膜太阳光反射率最高可达97.68%,平均发射率最高可达92.78%,在保持高反射率的同时兼具良好的中红外发射能力。
Smart Images

Figure CN122878722A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of functional polymer materials technology, specifically to passive radiation-cooled polymer films induced by rapid phase separation and their preparation methods. Background Technology
[0002] Driven by both global warming and the demand for building energy efficiency, passive daytime radiative cooling technology has attracted significant attention due to its zero-energy heat dissipation characteristics. The core requirement of this technology is that the materials must simultaneously possess high solar reflectivity (0.3-2.5µm) and high emissivity in the atmospheric window wavelength range (8-13µm). However, in pursuing optical performance, existing radiative cooling materials generally prioritize manufacturing convenience and cost, neglecting to incorporate life-cycle environmental friendliness, green processes, and material recyclability into their design considerations. This leads to significant sustainability obstacles for large-scale applications.
[0003] To meet the aforementioned spectral requirements, existing technologies mainly follow two routes. The first is a multilayer photonic structure or metal reflective backplane stacking scheme, which involves alternating deposition of dielectric films with different refractive indices using vacuum deposition processes such as electron beam evaporation and magnetron sputtering, or coating a high-infrared-emission polymer layer onto a polished metal layer. While this approach achieves extremely high spectral selectivity, it suffers from high energy consumption, expensive equipment, and the metal layer is prone to corrosion. Furthermore, the multilayer heterogeneous structure is difficult to recycle or degrade economically after disposal. The second approach is a particle-filled composite coating scheme, which disperses high-refractive-index inorganic particles (such as TiO2 and BaSO4) in an organic resin matrix at a volume ratio exceeding 60%. This utilizes particle scattering to reflect sunlight and provides infrared emission through phonon resonance. However, the ultra-high filling ratio easily leads to particle agglomeration and poor dispersion uniformity. The coating thickness typically needs to reach hundreds of micrometers, resulting in insufficient mechanical strength and a surface susceptible to contamination. More importantly, the resin matrix is mostly a non-degradable petroleum-based polymer. After solidification with inorganic particles, it forms an irreversible cross-linked organic-inorganic composite structure, which cannot be naturally degraded or separated and recycled, ultimately leading to landfill or incineration. Both of the above technical routes face the same core contradiction: the acquisition of high optical performance always comes at the cost of environmental friendliness, green process, or material recyclability.
[0004] To address the aforementioned problems, this invention provides a rapidly phase-separation-induced passive radiation cooling polymer thin film and its preparation method. This method uses a single polymer as the raw material and a low-toxicity solvent as the processing medium, requiring no addition of any inorganic functional fillers. Phase separation is induced solely through a good solvent-poor solvent blend system, enabling the in-situ formation of a three-dimensional porous structure with efficient light scattering and infrared radiation conduction capabilities within the thin film. This simultaneously achieves excellent optical properties, a simple preparation process, environmental friendliness throughout its entire lifecycle, and closed-loop material recycling. Furthermore, it provides a universal preparation platform for various polymer systems. Summary of the Invention
[0005] In the field of radiation cooling materials, this paper solves the problems of complex preparation processes, non-biodegradability or difficulty in recycling, and trade-offs between spectral performance and sustainability of existing radiation cooling materials. It provides a simple, universal, recyclable, high-performance radiation cooling thin film and its preparation method.
[0006] To achieve the above objectives, the technical solution of the present invention is as follows:
[0007] A rapidly phase-separation-induced passive radiation-cooled polymer film, the film being composed of a single polymer component and having an internal porous structure formed by non-solvent-induced phase separation; the film exhibits a solar reflectivity ≥92% in the 0.3–2.5 µm wavelength range and an infrared emissivity ≥90% in the 8–13 µm atmospheric window wavelength range.
[0008] Furthermore, the porous structure is a multi-level micro-nano pore network with a pore size distribution range of 127~2407 nm.
[0009] Furthermore, the polymer is any one of polybutylene terephthalate, polycaprolactone, poly-β-hydroxybutyric acid, polybutylene succinate, polylactic acid, polycarbonate, polystyrene, or thermoplastic polyurethane.
[0010] A method for preparing passively radiatively cooled polymer films induced by rapid phase separation includes the following:
[0011] Dissolve the polymer in a good solvent to prepare a polymer solution with a mass concentration of 10% to 30%;
[0012] Under stirring conditions, a poor solvent is added dropwise to the polymer solution, with a volume ratio of poor solvent to good solvent of 1:(2~6). Stirring continues until the mixture is homogeneous, resulting in a polymer mixed solution.
[0013] The polymer mixture solution is coated into a film and allowed to dry at room temperature to obtain a polymer film.
[0014] Furthermore, the droplet acceleration rate of the undesirable solvent is 0.5~2 mL / min.
[0015] Furthermore, the polymer is any one of polybutylene terephthalate, polycaprolactone, poly-β-hydroxybutyric acid, polybutylene succinate, polylactic acid, polycarbonate, polystyrene, or thermoplastic polyurethane.
[0016] Furthermore, the good solvent is dichloromethane or tetrahydrofuran, and the poor solvent is anhydrous ethanol.
[0017] Furthermore, the stirring speed is 600~800 r / min.
[0018] Furthermore, the stirring time should be continued for 0.5 to 2 hours.
[0019] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0020] High solar reflectance performance. The pure polymer porous film prepared by this invention has a solar reflectance of up to 97.68% and an average emissivity of up to 92.78%, maintaining high reflectance while also having good mid-infrared emission capability.
[0021] Excellent outdoor radiative cooling performance. The pure polymer film prepared by this invention was quantitatively tested using a standardized outdoor radiative cooling performance testing platform. Among them, the polybutylene terephthalate-adipate film achieved an average daytime temperature drop (compared to ambient temperature) of 13.69℃.
[0022] Environmentally friendly throughout its entire life cycle. The film is composed of a single biodegradable polymer without any added inorganic functional fillers. It can gradually break down and eventually degrade under soil burial conditions. It is environmentally friendly throughout the entire process from raw materials, preparation, use to disposal, avoiding the problems of microplastic generation and recycling difficulties after disposal from the source.
[0023] Closed-loop recycling. Waste films can be redissolved in a good solvent, and through a solvent-inducing phase separation method, followed by coating, drying, and molding, porous films can be remade. To verify this regeneration performance, 40 dissolution-reconstruction cycles were conducted on various biodegradable polymer films, and the solar reflectance of the films after each cycle was measured. The results show that the optical performance of the films after 40 cycles of regeneration has a small decline, and the reflectance can be maintained at an excellent level (>90%). For the other three engineering polymer films, after 10 dissolution-reconstruction cycles, their solar reflectance can also be maintained above 90%, all exhibiting good cycle stability.
[0024] Excellent material versatility. The method of this invention is not only applicable to biodegradable polymers such as polybutylene terephthalate (PET), but also to common engineering plastic substrates such as thermoplastic polyurethane, polycarbonate, and polystyrene. Similar porous structures and high reflectivity can be obtained simply by adjusting the type and ratio of solvent, providing a universal preparation platform for radiative cooling materials. Attached Figure Description
[0025] Figure 1 This is a process flow diagram of the present invention.
[0026] Figure 2 SEM images for examples and comparative examples.
[0027] Figure 3 Examples and comparative examples show solar reflectance and infrared emission spectra, (a, b) different non-solvent ratios; (c, d) various biodegradable polymer films; (e, f) engineered polymer films.
[0028] Figure 4 For outdoor passive radiative cooling testing of thin films, (a) schematic diagram and physical image of the outdoor testing device; (b, c) time-series curves of biodegradable polymer film and ambient temperature, and corresponding temperature difference change curves; (d, e) time-series curves of engineering plastic film and ambient temperature, and corresponding temperature difference change curves. Figure 5 The macroscopic morphology of the films after multiple dissolution-film formation cycles is shown in (a) the film of Example 2 (0 to 40 cycles); and (b) the film of Example 8 (0 to 10 cycles). Detailed Implementation
[0029] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0030] The preparation process of this invention is as follows: Figure 1 As shown, the specific implementation steps are as follows:
[0031] S1 involves slowly adding the pretreated and dried polymer particles in batches to a light-proof beaker containing a good solvent. Large-scale addition at once is prohibited to avoid particle agglomeration, localized accumulation, and uneven solute dissolution. The entire operation is conducted at room temperature and pressure in the dark, with a constant stirring rate of 200-800 r / min, and continuous stirring at a constant temperature for 2 hours until the polymer is fully dissolved, resulting in a homogeneous and transparent polymer solution, which is then allowed to stand for later use.
[0032] S2. The unsuitable solvent is added dropwise to the polymer solution at a constant low rate; continuous and uniform stirring is maintained throughout the addition process, and the dropping rate is strictly controlled to be maintained at 0.5-2 mL / min. -1 After all the undesirable solvent has been added, continue stirring at a constant temperature for 1 hour to finally obtain a homogeneous polymer mixture solution.
[0033] Before the S3 film formation process, a standardized pretreatment procedure is performed on the substrate, which includes dust removal, oil removal, deionized water rinsing, and constant temperature air drying. This ensures that the substrate surface has uniform cleanliness, flatness, and adhesion. The homogeneous mixed solution obtained above is then steadily and quantitatively poured into the central forming area of the horizontally placed substrate, and a high-precision coating blade is used for uniform dynamic coating.
[0034] After the S4 film is coated, it is left to dry in a closed environment with constant room temperature and humidity until the solvent has completely evaporated and the film has solidified. This yields a polymer film formed by phase separation induced by a good-non-solvent blending system.
[0035] Example 1
[0036] S1 The polymer particles were dried in a vacuum drying oven at 60 °C for 10 h to remove adsorbed moisture and volatile impurities from the raw materials. Then, they were taken out and cooled to room temperature. 50 g of pretreated polybutylene terephthalate-adipate granules were slowly added in three batches to a light-proof beaker containing 343 mL of dichloromethane under normal temperature, normal pressure and light-proof environment. The addition time of each batch was controlled within 5 min to avoid excessive local concentration, which would lead to agglomeration or insoluble matter formation. The mixture was stirred at 800 r / min for 2 h until a homogeneous and transparent polymer solution was obtained and allowed to stand for later use.
[0037] In step S2, 57 mL of anhydrous ethanol was added dropwise to the polymer solution prepared in step S1 at a rate of 2 mL / min. Continuous stirring at a constant speed of 800 r / min was maintained throughout the addition. After all the anhydrous ethanol had been added, stirring was continued at a constant temperature for 1 h to obtain a homogeneous poly(butylene terephthalate)-poly(butylene adipate) mixed solution.
[0038] Before the S3 film-forming process, a standardized pretreatment procedure is performed on the PET film substrate, which includes dust removal, oil removal, deionized water rinsing, and constant temperature air drying. This ensures that the substrate surface has uniform cleanliness, flatness, and adhesion. The phase mixture solution obtained in step S2 is poured in sufficient quantity into the central forming area of the horizontally placed substrate. After the solution has naturally leveled, a stainless steel single-sided coater is used as a high-precision coating blade to dynamically coat the film at a uniform speed of 0.5 m / s. The wet film thickness is limited by controlling the distance between the blade and the substrate to 1000 µm. After drying, the dry film thickness is measured to be 124.3 µm.
[0039] After the S4 film is coated, it is left to dry in a closed environment at 25°C and 50% humidity until the solvent has completely evaporated and the film has solidified. This yields a polymer film based on a dichloromethane-anhydrous ethanol (volume ratio 6:1) solvent system.
[0040] Example 2
[0041] 50 g of polybutylene terephthalate-adipate granules, 300 mL of dichloromethane, 100 mL of anhydrous ethanol, the distance between the doctor blade and the substrate was 1000 µm, the film thickness after drying was 104.38 µm, and other parameters were the same as in Example 1.
[0042] Example 3
[0043] 50 g of polybutylene terephthalate (PET), 267 mL of dichloromethane, 133 mL of anhydrous ethanol, a doctor blade spacing of 1000 µm, and a film thickness of 163.12 µm after drying were used, with other parameters the same as in Example 1.
[0044] Example 4
[0045] 100g polycaprolactone granules, 600 mL dichloromethane, 200 mL anhydrous ethanol, the distance between the doctor blade and the substrate was 1000µm, the film thickness after drying was 116.93 µm, and other parameters were the same as in Example 1.
[0046] Example 5
[0047] 100 g of poly-β-hydroxybutyric acid particles, 600 mL of dichloromethane, 200 mL of anhydrous ethanol, the distance between the doctor blade and the substrate was 1000 µm, the film thickness after drying was 108.19 µm, and other parameters were the same as in Example 1.
[0048] Example 6
[0049] 100g of polybutylene adipate granules, 600 mL of dichloromethane, 200 mL of anhydrous ethanol, the distance between the scraper and the substrate was 1000 µm, the film thickness after drying was 118.64 µm, and other parameters were the same as in Example 1.
[0050] Example 7
[0051] 100 g polylactic acid particles, 600 mL dichloromethane, 200 mL anhydrous ethanol, the distance between the doctor blade and the substrate was 1000 µm, the film thickness after drying was 128.4 µm, and other parameters were the same as in Example 1.
[0052] Example 8
[0053] 150 g polycarbonate particles, 730 mL dichloromethane, 240 mL anhydrous ethanol, the distance between the doctor blade and the substrate was 1000 µm, the film thickness after drying was 107.83 µm, and other parameters were the same as in Example 1.
[0054] Example 9
[0055] 200 g polystyrene particles, 700 mL dichloromethane, 220 mL anhydrous ethanol, the distance between the doctor blade and the substrate was 1000 µm, the film thickness after drying was 122.45 µm, and other parameters were the same as in Example 1.
[0056] Example 10
[0057] 200 g polyurethane particles, 1200 mL tetrahydrofuran, 1200 mL anhydrous ethanol, the distance between the doctor blade and the substrate was 1000 µm, the film thickness after drying was 110.86 µm, and other parameters were the same as in Example 1.
[0058] Comparative Example 1
[0059] 50 g of polybutylene terephthalate (PET) particles, 400 mL of dichloromethane, a doctor blade spacing of 1000 µm between the doctor blade and the substrate, and a film thickness of 83.00 µm after drying. No unsuitable solvents were added. Other procedures were the same as in Example 1.
[0060] Comparative Example 2
[0061] 50 g of polycaprolactone granules, 400 mL of dichloromethane, a doctor blade spacing of 1000 µm between the doctor blade and the substrate, and a film thickness of 87.67 µm after drying. No unsuitable solvents were added. Other procedures were the same as in Example 1.
[0062] Comparative Example 3
[0063] 50 g of poly-β-hydroxybutyric acid particles, 400 mL of dichloromethane, a doctor blade spacing of 1000 µm between the doctor blade and the substrate, and a film thickness of 89.41 µm after drying. No unsuitable solvents were added. Other procedures were the same as in Example 1.
[0064] Comparative Example 4
[0065] 50 g of polybutylene adipate granules, 400 mL of dichloromethane, a doctor blade spacing of 1000 µm between the doctor blade and the substrate, and a film thickness of 85.37 µm after drying. No unsuitable solvents were added. Other procedures were the same as in Example 1.
[0066] Comparative Example 5
[0067] 50 g polylactic acid granules, 400 mL dichloromethane, a doctor blade spacing of 1000 µm between the doctor blade and the substrate, and a film thickness of 83.94 µm after drying. No unsuitable solvents were added. Other procedures were the same as in Example 1.
[0068] Comparative Example 6
[0069] 150 g of polycarbonate particles, 730 mL of dichloromethane, a doctor blade spacing of 1000 µm between the doctor blade and the substrate, and a film thickness of 85.75 µm after drying. No unsuitable solvents were added. Other procedures were the same as in Example 1.
[0070] Comparative Example 7
[0071] 150 g polystyrene particles, 700 mL dichloromethane, a doctor blade spacing of 1000 µm between the doctor blade and the substrate, and a film thickness of 84.11 µm after drying. No undesirable solvents were added. Other procedures were the same as in Example 1.
[0072] Comparative Example 8
[0073] 200 g polyurethane particles, 1200 mL tetrahydrofuran, a doctor blade spacing of 1000 µm between the doctor blade and the substrate, and a film thickness of 86.10 µm after drying. No undesirable solvents were added. Other procedures were the same as in Example 1.
[0074] Test Results
[0075] SEM results
[0076] like Figure 2 As shown, for the series of films prepared with different non-solvent ratios in the above embodiments and comparative examples, scanning electron microscope images clearly recorded the significant structural changes as the non-solvent content increased. Under the determined optimal ratio (Example 2), the film spontaneously forms a dense multi-level micro-nano pore network. This native porous microstructure can significantly enhance the system's scattering and reflection efficiency in the solar light band and construct a continuous infrared radiation conduction path, providing core microstructure support for the material to possess excellent passive radiative cooling properties.
[0077] Meanwhile, this formulation strategy was extended to the other four biodegradable polymers, and the films obtained in Examples 4, 5, 6 and 7 were all dense porous micro-nano pore networks.
[0078] It is worth noting that, for general engineering plastics, similar porous morphologies can also be constructed in Examples 8, 9, and 10 simply by adjusting the solvent system and ratio.
[0079] Table 1 Summary of aperture distribution ranges for each embodiment
[0080] Example 1 774-1582 nm Example 2 540-2407 nm Example 3 127-989 nm Example 4 426-2460 nm Example 5 531-2380 nm Example 6 511-2415 nm Example 7 1389-16819 nm Example 8 378-8169 nm Example 9 364-14336 nm Example 10 1860-15565 nm
[0081] Optical spectral characterization
[0082] The system tested the solar reflectance performance of the examples and comparative examples. The light reflectance of the thin film is highly sensitive to the solvent ratio; Example 2, with its optimal ratio, achieves excellent broad-spectrum solar reflectance and possesses high reflectivity, such as... Figure 3 As shown in Figure a. Example 2 with the optimal formulation maintains an extremely high infrared emissivity of 0.9244 within the atmospheric window region, as... Figure 3 As shown in b. Applying the optimal formulation to other single polymer systems, such as Examples 4, 5, 6, and 7, all yielded excellent solar reflectance and infrared emissivity, as shown in examples b. Figure 3 c, 3d are shown.
[0083] Table 2 shows the test results of solar reflectivity and infrared emissivity for each embodiment and Comparative Example 1.
[0084] Example 1 79.10 85.79 Example 2 97.68 92.44 Example 3 89.42 86.17 Example 4 97.52 92.03 Example 5 97.37 92.53 Example 6 96.17 92.78 Example 7 93.53 90.02 Example 8 94.44 90.85 Example 9 91.78 90.97 Example 10 92.91 90.46 Comparative Example 1 19.00 79.20
[0085] Daytime radiative cooling performance test
[0086] Referring to existing publicly available literature on outdoor testing protocols, we independently constructed an outdoor testing platform suitable for long-term field testing of thin-film cooling performance, such as... Figure 4 As shown in Figure a. By collecting environmental and sample temperature data, the excellent radiative cooling effect of the material of this invention was verified. The relevant experimental results are recorded below, as follows. Figure 4 As shown in b and 4c. In Example 2, the porous film achieved an average daytime temperature drop of 13°C. The biodegradable films in the other examples also achieved significant temperature drops. Therefore, the porous film samples of this invention possess a stable daytime cooling effect. Furthermore, films prepared from common engineering plastics using this rapid, non-solvent-induced phase separation strategy also exhibit stable daytime cooling effects, such as... Figure 4 As shown in d and 4e.
[0087] Table 3. Average temperature drop data of passive radiation cooling samples in each embodiment during outdoor testing.
[0088] Example 2 13.69 Example 4 12.56 Example 5 9.82 Example 6 13.95 Example 7 9.67 Example 8 7.4 Example 9 7.8 Example 10 9.7
[0089] Thin film regeneration and recycling
[0090] Example 2 describes the preparation of a porous thin film that achieves excellent radiative cooling optical properties without any inorganic fillers. The material is completely biodegradable, retaining >90% of its properties after 40 dissolution-film formation cycles, with no significant change in macroscopic morphology. Figure 5 As shown in a. This truly achieves a closed-loop, cyclical design.
[0091] The steps for recycling and regenerating waste film are as follows:
[0092] Waste membranes after use are collected directly. After removing visible impurities, they are soaked and washed several times with anhydrous ethanol, and then dried in a vacuum drying oven at 60 °C for 10 h to fully remove residual solvents and adsorbates. The dried waste membranes are added to dichloromethane in a certain proportion and stirred until completely dissolved to obtain a homogeneous regenerated polymer solution. Subsequently, anhydrous ethanol is added dropwise to this regenerated solution in the same volume ratio as the initial preparation to induce a solvent-free phase separation. The stirring rate, dropping rate, and environmental conditions are maintained consistent with the initial preparation. After thorough mixing, the mixture is coated again and allowed to dry and cure at room temperature to obtain the regenerated porous membrane. This process enables closed-loop recycling of the material.
[0093] Furthermore, the thin film obtained in Example 8 also exhibits excellent radiation-cooling optical properties, retaining over 90% of its performance after 10 dissolution-film formation cycles, and maintaining a stable macroscopic structure. Figure 5 As shown in b, this also achieves closed-loop recycling of materials.
[0094] Table 4 shows the solar spectral reflectance test results of different samples after multiple dissolution-film formation processes.
[0095] Example 2 Repeat 40 times 91.88 Example 4 Repeat 40 times 91.78 Example 5 Repeat 40 times 91.59 Example 6 Repeat 40 times 91.53 Example 7 Repeat 40 times 90.45 Example 8 Repeat 10 times 92.61 Example 9 Repeat 10 times 90.03 Example 10 Repeat 10 times 90.56
[0096] Based on the above-described preferred embodiments of the present invention, and through the foregoing description, those skilled in the art can make various changes and modifications without departing from the inventive concept. The technical scope of this invention is not limited to the contents of the specification.
Claims
1. A rapidly phase-separation-induced passive radiation-cooled polymer thin film, characterized in that, The film is composed of a single polymer component and has a porous structure formed by non-solvent-induced phase separation. The film has a solar reflectance of ≥92% in the 0.3~2.5 µm band and an infrared emissivity of ≥90% in the 8~13 µm atmospheric window band.
2. The polymer film according to claim 1, characterized in that, The porous structure is a multi-level micro-nano pore network with a pore size distribution range of 127~2407 nm.
3. The passive radiation cooling polymer film according to claim 1, characterized in that, The polymer is any one of polybutylene terephthalate, polycaprolactone, poly-β-hydroxybutyric acid, polybutylene succinate, polylactic acid, polycarbonate, polystyrene, or thermoplastic polyurethane.
4. A method for preparing a rapidly phase-separation-induced passive radiation-cooled polymer thin film, characterized in that, Includes the following: Dissolve the polymer in a good solvent to prepare a polymer solution with a mass concentration of 10% to 30%; Under stirring conditions, a poor solvent is added dropwise to the polymer solution, with a volume ratio of poor solvent to good solvent of 1:(2~6). Stirring continues until the mixture is homogeneous, resulting in a polymer mixed solution. The polymer mixture solution is coated into a film and allowed to dry at room temperature to obtain a polymer film.
5. The preparation method according to claim 4, characterized in that, The droplet rate of undesirable solvents is 0.5~2 mL / min.
6. The preparation method according to claim 4, characterized in that, The polymer is any one of polybutylene terephthalate, polycaprolactone, poly-β-hydroxybutyric acid, polybutylene succinate, polylactic acid, polycarbonate, polystyrene, or thermoplastic polyurethane.
7. The preparation method according to claim 4, characterized in that, The good solvent is dichloromethane or tetrahydrofuran, and the bad solvent is anhydrous ethanol.
8. The preparation method according to claim 4, characterized in that, The stirring speed is 600~800 r / min.
9. The preparation method according to claim 4, characterized in that, Continue stirring for 0.5 to 2 hours.